2012
DOI: 10.1371/journal.pone.0047110
|View full text |Cite|
|
Sign up to set email alerts
|

Small-Molecule Quinolinol Inhibitor Identified Provides Protection against BoNT/A in Mice

Abstract: Botulinum neurotoxins (BoNTs), etiological agents of the life threatening neuroparalytic disease botulism, are the most toxic substances currently known. The potential for the use as bioweapon makes the development of small-molecule inhibitor against these deadly toxins is a top priority. Currently, there are no approved pharmacological treatments for BoNT intoxication. Although an effective vaccine/immunotherapy is available for immuno-prophylaxis but this cannot reverse the effects of toxin inside neurons. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…To date, only a few publications have shown beneficial treatment of botulism with experimental INABDs [21,[27][28][29][30][31][32][33][34]. Due to the absence of approved INABDs, the proof of concept of our model, in terms of measuring the beneficial effects of potential anti-BoNT/A compounds, was assessed by pharmaceutical antitoxin.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few publications have shown beneficial treatment of botulism with experimental INABDs [21,[27][28][29][30][31][32][33][34]. Due to the absence of approved INABDs, the proof of concept of our model, in terms of measuring the beneficial effects of potential anti-BoNT/A compounds, was assessed by pharmaceutical antitoxin.…”
Section: Discussionmentioning
confidence: 99%
“…These IC 50 values are consistent with previous studies that reported lowmicromolar IC 50 values. 26,35,38 Using these compounds as a starting point, this series has been expanded and detailed structure−activity and ADME studies have been performed. 37 Next, we determined the potency of 27 spiro(indolthiadiazole) compounds (1 hit and 26 additional structures) available from the ChemBridge small molecule repository.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Several small molecule HTS campaigns with recombinant LC/A (rLC/A) have been described, although the majority of inhibitory compounds initially identified possess poor (i.e., micromolar) inhibitory constants ( K i ). More recently, inhibitory compounds with submicromolar K i values have been reported, including a betulin-derived triterpenoid with a K i of 800 nM, a quinolinol inhibitor with an estimated IC 50 of 40 nM in a rat synaptosomal model, and a “hybrid” small molecule with a K i of 600 nM . Several potent hydroxamate inhibitors have been reported, including 2,4-dichlorocinnamic hydroxamate ( K i = 300 nM), a related benzothiophene hydroxamic acid ( K i = 77 nM), and a recently reported adamantine hydroxamate ( K i = 27 nM) .…”
Section: Introductionmentioning
confidence: 99%
“…In order to further test the inhibitory effect of the most promising peptide inhibitors, a mouse model test was performed as previously reported 44 . Six-week-old female BALB/c mice were used in all the assays.…”
Section: Methodsmentioning
confidence: 99%